Sexual harassment in the education sector: a Malaysian perspective - Ali Mohamed, Ashgar Ali (IIUM Press, 2016)
Sexual harassment is one of the contemporary silent issues in the education sector in Malaysia. Despite the advocacy of no discrimination between male and female in education, sexual harassment in schools, universities and colleges has drastically prevalent. More importantly, of greater challenges is the inadequate and ineffective measure to eradicate sexual harassment in schools and institutions of higher learning in the Malaysian context. Admittedly, it has been reiterated that schools need to promote the values of the larger society. Indeed, one of the primary objectives of institutions of learning is to promote social norms, ethical values and desirable behaviours. Therefore, the teachers' commitment and students' engagement in the process of teaching and learning should revolve round the portrayal of good behaviour and moral values.